(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Contributions of the Current Penal Code Regarding the Protection of Religious Freedom The criminal code is by far the richest source of criminal law. The purpose of criminal law or its mission is to defend and preserve the most important social values, without which a society cannot exist. Together with the fundamental law, the Constitution, the Criminal Code is a real instrument of the state of education of citizens in the spirit of compliance with the rules imposed, so as to ensure a favorable social framework in developing and preserving values and social relations absolutely necessary for the development of any human society. The link between the Criminal Code and religious freedom is extremely strong, in the sense that it defends, by criminalizing dangerous acts, religious freedom, as a social value of great importance in contemporary society and beyond. Therefore, criminal law is one of the most important branches of the legal system.